The Impact Of The Islamic Faith In Developing Islamic Civilization And Guiding Behavior (Journal of the College of Basic Education, 2024)
Praise be to God, and may blessings and peace be upon the Messenger of God, his family, his companions, and those who follow him.This research aims to reveal and clarify the impact of the Islamic belief in developing civilization and directing behavior, with reference to the Book of God and the Sunnah of His Messenger, peace and blessings be upon him. Ethics or correct behavior is what develops civilization. This has been confirmed by rational and transmissional evidence. The Islamic belief also confirms that man lives his life in this world. Life is considered a passing stage and is a period of testing and testing, and that this world is a testing ground, and that his true life will be in the Hereafter in which all people will be rewarded for their deeds in this world on the Day when people will rise up before the Lord of the Worlds. Human behavior is the reflection of the soul on its owner, and the overflow of its source. It shines and darkens, depending on the goodness or wickedness of the soul, its integrity or deviation. There is no reprehensible creation that does not have one of the causes of the soul’s vileness or deviation. Among the worst human qualities are arrogance and arrogance, which are two qualities that have a negative effect. On the individual himself, his relationships with others, and on civilization as well.Research problem:The problems of research lie in the impact of the Islamic faith in developing civilization and directing behavior, which is one of the important problems in society, as civilization advances and is elevated by right behavior stemming from the Islamic faith.The importance of the topic and the reason for choosing it:Explaining “the impact of the Islamic faith in developing Islamic civilization and guiding behavior” by implanting the religious motive that helps him control the individual’s behavior and get closer to God, peace be upon him, to reach refined morals by which the human soul rises above vices and flourishes and grows civilization through it. The reason for choosing the topic is self-preservation. Mankind is protected from Satan's insinuations by strengthening the value of the Islamic religion in directing human behavior by implanting the Islamic doctrine that directs human behavior and enhances Islamic civilization.Research objectives and hypothesis:The research aims primarily to identify the concept of human behavior, which in turn leads to the development of civilization through the influence of the Islamic faith represented by the Book of God and the Sunnah of His Messenger, may God bless him and grant him peace, and to highlight this sound approach to reaching the finest civilizations. It also aims to strengthen man's relationship with his God by educating the Muslim individual in correct behavior through the Islamic faith.